Understanding the Motif Meaning of Dermayon Batik as Womenâs Expression - Prawira, Nanang Ganda (TAWARIKH, 2014)
ABSTRACT: Indonesian traditional culture has many kind of forms and types of craft. The culture proves the existence of the same creative expression with the newness. The craftsmen of batik consist of workers, both men and women in a group or family. This article describes the creativity developed by Paoman villager in Indramayu Regency, West Java, Indonesia, to the âDermayon Batikâ (batik style of Indramayu). In this case, women are more dominant in processing to create the batik, especially the technique to make handmade batik (traditional). Hence, what is called with the âDermayon Batikâ is identical to the womenâs work, it is because their visualization has become identity of the feminity. Motif of Indramayuâs Batik, which coastal character in generally, not only describes nature, social, and culture of fisherman, but also reflects the mood of the women. Women are clearly express their mood in spots, lines, shapes, and aesthetic structurals in motif of âDermayon Batikâ. The aesthetic expression, which dynamic and meaningfull culture, is a reflection of the women related to the genre of the motif. In expressing this âDermayon Batikâ, it is used cultural studies, aesthetic, and semiotic-interpretative approach. However, a manifestation of the womenâs creativity in âDermayon Batikâ since a long time until now. Inheritance of âDermayon Batikâ in a family is traditional educational values, which now begin to threatened its survival. Finally, in the planning and implementation of art education, as creative education, is appropriate based on an understanding of cultural traditions (local) growing in the community.KEY WORDS: Cultural study, femininity, expression, aesthetic, semiotic, âDermayon Batikâ, womenâs work, coastal character, and art education.About the Author: Dr. Nanang Ganda Prawira is a Senior Lecturer at the Department of Fine Arts Education, Faculty of Language and Art Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. For academic interests, the author can be contacted via e-mail at: nanangganda@yahoo.comHow to cite this article? Prawira, Nanang Ganda. (2014). âUnderstanding the Motif Meaning of Dermayon Batik as Womenâs Expressionâ in TAWARIKH: International Journal for Historical Studies, Vol.6(1) October, pp.105-120. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (August 16, 2013); Revised (April 10, 2014); and Published (October 28, 2014).